2012
DOI: 10.1038/aps.2011.177
|View full text |Cite
|
Sign up to set email alerts
|

Strontium fructose 1,6-diphosphate prevents bone loss in a rat model of postmenopausal osteoporosis via the OPG/RANKL/RANK pathway

Abstract: Aim: To evaluate the protective effects of strontium fructose 1,6-diphosphate (FDP-Sr), a novel strontium salt that combined fructose 1,6-diphosphate (FDP) with strontium, on bone in an ovariectomy-induced model of bone loss. Methods: Eighty female Sprague-Dawley rats were ovariectomized (OVX) or sham-operated. Three months later, the rats were assigned to six groups (10 for each): sham-operated, OVX control, OVX+FDP-Sr (110, 220, or 440 mg/kg), or OVX+strontium ranelate (SR, 180 mg/kg). Drugs were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…During osteoclastogenesis, RANKL drives osteoclast differentiation (20) while OPG antagonizes RANKL action (21), and the RANKL/OPG ratio determines osteoclastogenesis in the bone. Here, we showed that both STZ and OVX increased RANKL/OPG ratio, which is consistent with previous studies (30)(31)(32)(33). Liraglutide significantly reduced RANKL/OPG ratio compared to the untreated counterparts, indicating that liraglutide can inhibit osteoclastogenesis in STZ, OVX and STZ+OVX rats.…”
Section: Discussionsupporting
confidence: 92%
“…During osteoclastogenesis, RANKL drives osteoclast differentiation (20) while OPG antagonizes RANKL action (21), and the RANKL/OPG ratio determines osteoclastogenesis in the bone. Here, we showed that both STZ and OVX increased RANKL/OPG ratio, which is consistent with previous studies (30)(31)(32)(33). Liraglutide significantly reduced RANKL/OPG ratio compared to the untreated counterparts, indicating that liraglutide can inhibit osteoclastogenesis in STZ, OVX and STZ+OVX rats.…”
Section: Discussionsupporting
confidence: 92%
“…B-ALP and NTx of rats in OVX group significantly increased since the 12 th week (P<0.05) and 9 th week (P<0.05) post operation, respectively, compared with those in Sham group(shown in Figure 1A and 1B). The results indicated that OVX rat had the characteristic of bone high turnover rate according to the previous reports [29], [30].…”
Section: Resultssupporting
confidence: 80%
“…BMD of the lumbar vertebrae (L1–L5) and left femur from anesthetized rats was measured (isoflurane) by dual-energy X-ray absorptiometry (GE, Lunar ProdigyTM) at the 12 th 24 th week post-operation. BMD was calculated by dividing the measured area by the bone mineral content (BMC), as previously reported [30]. Baseline of BMD was determined 1 week before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, several researchers clarified a significant increase in CTX after OVX [29]. Similarly, several researchers clarified a significant increase in CTX after OVX [29].…”
Section: Gomori's Trichrome Stainmentioning
confidence: 92%